Organizational Change Management in Higher Education through the Lens of Executive Coaches - Dimitrios Vlachopoulos (MDPI AG, 2021)
This study investigated perceptions of organizational change management among executive coaches working with British higher-education leaders and factors that make leaders effective when managing change. This basic qualitative research used semi-structured interviews with eight executive coaches selected through purposeful sampling. As main challenges to efficient, inclusive change management, participants mentioned leaders' lack of a strategic vision or plan, lack of leadership and future leader development programs, and lack of clarity in decision-making. They recognized that leaders' academic and professional profiles are positively viewed and said that, with coaching and support in leadership and strategic planning, these people can inspire the academic community and promote positive change. Additional emphasis was given to the role of coaching in the development of key soft skills (honesty, responsibility, resiliency, creativity, proactivity, and empathy, among others), which are necessary for effective change management and leadership in higher education. The paper's implications have two aspects. First, the lessons of the actual explicit content of the coaches' observations (challenges to efficient change management and views of leaders); second, the implications of these observations (how coaching can help and what leaders need).